PENERAPAN STRATEGI PEMBELAJARAN AKTIF GROUP TO GROUP EXCHANGE (GGE) UNTUK MEMOTIVASI DAN MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIPA SMA NEGERI 1 KAMPAR - Novrianti, Reza; copriady, Jimmi; Susilawati, Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to determine the improvement of motivation and achievment of students on Reaction Rate subject in class XI MIPA SMAN 1 Kampar. The type of research is experimental research with Rendomize Control Group Pretest-Posttest design. The population of this study is the entire class XI MIPA SMAN 1 Kampar as many as 4 classes. Samples were determined based on normality test and homogeneity test, obtained by 2 classes that were normally distributed and randomly selected by students in class XI MIPA 1 as experimental class and learner in class XI MIPA 4 as control class. The experimental class is a class that applied GGE active learning strategy while control class is not applied GGE active learning strategy. The instrument of this research is a matter of understanding the matter of reaction rate and motivation questionnaire that has been tested Validity and reliabelitas, obtained valid and reliable data after testing. The result of hypothesis test of t-test obtained t of t table. t-test 2,65 for learning result and t-test3,68 for learning motivation with t table 1,67. It can be concluded that the implementation of GGE active learning strategy can increase motivate student’s and achievment on the subject matter of Reaction Rate. The influence of GGE application of active learning strategy to the learning outcomes of 26.6% and learning motivation of 12.2% with the relationship of learning outcomes and learning motivation of 34.7%.Keywords :Reaction Rate,Learning Outcomes,Learning Motivate, Group to Group Exchange (GGE)